Exploring the shift in newborn care practices among mothers and grandmothers in rural Odisha, India - a qualitative study - Livson Thomas; Sumitha Arun; Deepak Thomas Varughese; Christ Kamalini Soreng; B. Prativa Manjari; Prabhati S. Khosla; Dikhita K. Pani (BMC, 2024)
Abstract Background This study delves into newborn care and infant-feeding practices in rural Odisha, specifically focusing on the rural KBK + region of Odisha (Kalahandi-Bolangir-Koraput region), inhabited predominantly by Schedule Tribes and Schedule Castes individuals. There has been an improvement in the health indicators in these areas in recent times. In the background of improved health indicators in these areas, this research explores the current and changing newborn care practices and attempts to gain insight into people's perceptions of the factors that brought about the changes. Methods This qualitative study was conducted between February and July 2023 at Christian Hospital, Bissamcuttack in Odisha. The methodology involved focused group discussions with mothers and grandmothers. Results Analysis revealed healthy practices like exclusive breastfeeding till six months of age, appropriate timing of the first bath, and prompt healthcare-seeking behavior for minor illnesses among the mothers. The use of cow ghee or breast milk in a baby's eyes, the application of ash on the umbilical cord, and the use of herbal medicines for minor illnesses were practiced more by the grandmothers in the past and were not as popular among the mothers. It is noteworthy that the cultural practices to ward off the 'evil eye' were practiced by both mothers and grandmothers alike. Despite the influence of traditional cultural practices on the beliefs and norms of the community, the study identified a shift in health-seeking behavior, with increased reliance on healthcare providers and safe healthcare practices. The study identifies the pivotal role of Accredited Social Health Activists (ASHAs) as a bridge between the rural communities and the healthcare system. Conclusions This research provides valuable insights for healthcare providers aiming to enhance community-centric safe newborn care practices in rural settings. The emphasis is on the importance of understanding the current and changing local practices. This would help the healthcare providers to encourage healthy practices while eliminating the harmful practices related to newborn care through community workers like ASHA and Anganwadi workers.